Intensitas Pengungkapan Sustainability Report pada Kinerja Keuangan - Utariyani, Ni Putu Ayu; Wirajaya, I Gede Ary (E-Jurnal Akuntansi; Vol 33 No 1 (2023), 2023)
This study aims to determine the effect of the intensity of disclosure of sustainability report dimensions of economic, environmental and social on the company's financial performance. The research was conducted at the Indonesia Stock Exchange (IDX) with the 2017-2019 research period. The research population is all companies listed on the Indonesia Stock Exchange in 2017-2019 which published sustainability reports and annual reports as many as 53 companies. The number of samples used in the study were 24 companies with 72 observational samples. Data analysis technique used multiple linear regression analysis. The results of the study show that the sustainability report on the economic and social dimensions has a positive effect on financial performance. Meanwhile, the environmental dimension of the sustainability report has no effect on financial performance. Keywords: Sustainability Report; Economic Dimension; Environmental Dimension; Social Dimension; Return on Assets.